THE ROLE AND FUNCTIONS OF THE SCIENCE OF PHYSICAL CULTURE IN THE EDUCATION SYSTEM - Yormatov Gulomjon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
physical culture and science as science is taught in the education system educational this specific purpose functions. The aim of the science of physical culture physical maturation of the individual to reach the harmonious development of the nurturing them active participants of the democratic state, and to the defense of the motherland ready to do creative work that consists determined. In order to achieve this goal is of course to study the science of physical culture of the network, the implementation of scientific research and the results obtained by reference to the practice of teaching students is achieved. Through this, the members of the society of physical culture on knowledge, skills, and qualifications of developing it. In this article, the role of science in the education system of physical culture and objectives of the research are the scientific aspects.